1986
DOI: 10.1002/clc.4960091104
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between systolic time intervals and arterial blood pressure

Abstract: It has been suggested that systolic time intervals (STI) can be used to monitor the cardiac effects of antihypertensive treatments and also to evaluate hypertensive patients. STI changes observed in hypertensives have been ascribed to myocardial disease, although they could be due to the existence of a relationship between STI and blood pressure. A group of 37 subjects (18 normotensives and 19 hypertensives) with no signs of heart failure and left ventricular dysfunction were studied to examine the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This approximation was used in the derivation of Equation (6b) from Equation (6a), with P ART replacing X. The data series for peak arterial blood pressure P ART found in De Scalzi et al 18 provided support for this approximation. For normotensives, Var(X) / [E(X)] 2 = 12.4 2 / 128.6 2 = 0.0093, and for hypertensives it is 22.4 2 / 175.7 2 = 0.0163…”
Section: Appendixmentioning
confidence: 92%
See 1 more Smart Citation
“…This approximation was used in the derivation of Equation (6b) from Equation (6a), with P ART replacing X. The data series for peak arterial blood pressure P ART found in De Scalzi et al 18 provided support for this approximation. For normotensives, Var(X) / [E(X)] 2 = 12.4 2 / 128.6 2 = 0.0093, and for hypertensives it is 22.4 2 / 175.7 2 = 0.0163…”
Section: Appendixmentioning
confidence: 92%
“…The mathematical relationship between measured P ART and measured B ART can then be readily determined by curve fitting, which then allows calculation of B ART from any cuff-measured P ART .The duration of arterial systole B ART is known to increase with arterial blood pressure. In 1986, De Scalzi et al18 reported that normal subjects have significantly lower values of average B ART compared to hypertensives [341.7 ± 18.4 ms versus 355.1 ± 15.2 ms (p < 0.025)]. Hence, average B ART in hypertensives is approximately 4% longer than the B ART average in normotensives (355.1 ms /341.7 ms).…”
mentioning
confidence: 99%